Clinical Review of Antidiabetic Drugs: Implications for Type 2 Diabetes Mellitus Management - Chaudhury, Arun; Duvoor, Chitharanjan; Reddy Dendi, Vijaya Sena; Kraleti, Shashank; Chada, Aditya; Ravilla, Rahul; Marco, Asween; Shekhawat, Nawal Singh; Montales, Maria Theresa; Kuriakose, Kevin; Sasapu, Appalanaidu; Beebe, Alexandria; et al. (Frontiers in Endocrinology, 2017)
Type 2 diabetes mellitus (T2DM) is a global pandemic, as evident from the global cartographic picture of diabetes by the International Diabetes Federation (http://www.diabetesatlas.org/). Diabetes mellitus (DM) is a chronic, progressive, incompletely understood metabolic condition chiefly characterized by hyperglycemia. Either impaired insulin secretion, resistance to tissue actions of insulin or a combination of both are thought to be the commonest reasons contributing to the pathophysiology of T2DM, a spectrum of disease originally arising from tissue insulin resistance and gradually progressing to a state characterized by complete loss of secretory activity of the beta-cells of the pancreas. T2DM is a major contributor to the very large rise in the rate of non-communicable diseases affecting developed as well as developing nations. In this mini-review, we endeavor to outline the current management principles, including the spectrum of medications that are currently used for pharmacologic management, for lowering the elevated blood glucose in T2DM.